THE EFFECT OF THE COLLABORATIVE PROBLEM SOLVING ON LEARNING RESULT REVIEWED FROM THE ABILITY OF MATHEMATIC CRITICAL THINKING OF CLASS VII - Rinadin Rinadin (Universitas Ahmad Dahlan, 2020)
The low learning results of mathematics and the ability of critical thinking mathematically to mathematics in Junior High School (SMP) Muhammadiyah 3 Depok Class VII Sleman District of Academic Year 2019/2020 which is due to identifying, choosing a problem-solving strategy, making alternatives to problem-solving, classification a statement, and making students conclusions still confused, difficult and less thorough in solving math problems. The purpose of this research is to know whether there is and or whether a significant influence (1) model factors learning to the outcome of student mathematics learning, (2) factors factor in mathematical critical thinking students against learning outcomes of mathematics, (3) Interaction between learning models and the ability of critical thinking mathematically to students of student mathematics learning outcomes. The type of research used is the type of experimental research using Factorial Design. The factorial design used is two-two factorial design. The study population was all the SMP Muhammadiyah 3 Depok Class VII Sleman District of Academic Year 2019/2020 with a class VII A sample as the control class and class VII D as an experimental class. Data analysis techniques using ANAVA two lanes with a prerequisite analysis test use the normality test and homogeneity test. The hypothesis test uses variance analysis and is continued with the LSD test. Based on the two-lane analysis test, the first hypothesis influences the learning model of mathematics learning outcomes in SMP Muhammadiyah 3 Depok Class VII Sleman District of Academic Year 2019/2020. The second hypothesis shows an influence of critical mathematical thinking ability to study the mathematics results in SMP Muhammadiyah 3 Depok Class VII Sleman District of Academic Year 2019/2020. The third hypothesis shows the influence of interaction between learning models and mathematical critical thinking abilities. Based on the LSD test calculation, the learning model of Collaborative Problem Solving (CPS) combined with high mathematical critical thinking is most influential in mathematics students SMP Muhammadiyah 3 Depok Class VII Sleman District of Academic Year 2019/2020.